AB0035 TWO DIFFERENT ABNORMAL BEHAVIORS IN CD4+T LYMPHOCYTES IN FIBROMYALGIA PATIENTS AND FIBROMYALGIA ASSOCIATED TO SJÖGREN'S SYNDROME. (2nd June 2020) - Monserratsanz, J.; Movasat, A.; Sosa Reina, M. D.; Gomez Lahoz, A. M.; Bohórquez, C.; Pérez Gómez, A.; Ruiz, L.; Cabezas Leon, M. J.; Sánchez Atrio, A.; Albarrán, F.; Álvarez de Mon, M.
Abstract : Background: Primary fibromyalgia syndrome is a prevalent rheumatic condition characterized by widespread pain and whose etiopathogenesis is not well understood. Fibromyalgia can also be secondary to other rheumatic diseases like Sjogren's syndrome; however, its relation to this disease is unknown. It has been suggested that the immune system is involved in their pathogenesis. The role of activation stages and cytokines profiles of CD4+T lymphocytes in fibromyalgia or fibromyalgia secondary to Sjogren´s syndrome are completely unclear and could play a key role in the pathophysiology of these diseases. Objectives: The objective of this study is to investigate the counts and distribution of the CD4+T lymphocyte activation subsets and their pattern of cytokine production in women with primary fibromyalgia, fibromyalgia secondary to Sjogren´s, Sjogren´s syndrome and healthy controls (HC). The counts and distribution of naïve (TN ), central memory (TCM ), effector memory (TEM ) and effector (TE ) CD4+T lymphocyte subsets were analyzed in these diseases. Furthermore, we investigated their pattern of IL-4, IL-10, IL-17A, IFNγ, and TNFα production. Methods: Counts and distribution of CD4+T subsets (TN, TCM, TEM, TE) and their cytokine producing capacity were measured using multiparametric flow cytometry in peripheral blood mononuclear cells (PBMC) from 20 primary fibromyalgia, 15 fibromyalgia associated to Sjögren and 15 primary Sjögren patients and 15 female controls. Fibromyalgia and/or Sjögren's syndrome were diagnosed based on ACR criteria. CD4+T cell activation stages were analyzed by the expression of the CD3, CD4, CD45RA, CD27 and CCR7 antigens. Cytokine CD4+T producing cells subsets were assayed stimulating PBMC during 6 hours, fixed, permeabilized and simultaneously stained with IL-4, IL-10, IL-17A, IFNγ, and TNFα intracellular cytokines. Results: Fibromyalgia patients showed a significant increase in the CD4+T, TN and TCM cells counts with compared to fibromyalgia secondary to Sjogren, Sjogren´s syndrome and HC. The counts of IL-17A, IL-4 and IFNγ producing CD4+T cells were increased in fibromyalgia patients with respect to HC. However, only IL17A and IFNγ, but not IL-4 producing CD4+T lymphocytes were increased with respect fibromyalgia secondary to Sjogren. These alterations were due to an increment of TEM IL-17A, TCM and TEM IL-4 and TN TCM and TEM IFNγ producing CD4+T cell subsets in fibromyalgia patients. Furthermore, IFNγ producing CD4+T cells were decreased in fibromyalgia secondary to Sjogren´s with respect to fibromyalgia patients and HC. Counts of TN TNFα producing CD4+ T cells were increased in fibromyalgia with respect fibromyalgia secondary to Sjogren. IL-10 producing CD4+T cells were normal in fibromyalgia but decreased in fibromyalgia secondary to Sjogren. Conclusion: Fibromyalgia patients show an abnormal circulating activation stages of CD4+T cells, as well as, express unusual elevated counts of CD4+T cells producing IL-17A, IL-4 and IFNγ. These alterations could differentiate two different pathologic and inflammatory behaviors of the T cell compartment between fibromyalgia and fibromyalgia secondary to Sjogren patients. References: [1]T helper 1 response is correlated with widespread pain, fatigue, sleeping disorders and the quality of life in patients with fibromyalgia.. Guggino G et al, Clin Exp Rheumatol. 2019. [2]A Comparative Study of Fibromyalgia, Rheumatoid Arthritis, Spondyloarthritis, and Sjögren's Syndrome. Bucourt E et al, Pain Med. 2019 Disclosure of Interests: None declared